(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2022)
Herbal medicine is used by pregnant women in Uganda to achieve therapeutic goals like induction of labour and control of postpartum haemorrhage. This study aimed at finding out the prevalence and determinants of herbal medicine use during pregnancy by women in an urban tertiary hospital in Uganda. In this cross-sectional survey, 520 postpartum women participated after informed consent. Data on demographic characteristics and self-reported use/non-use of herbal medicine in the just ended pregnancy were collected. Using modified Poisson regression model, factors associated with use of herbal medicine in pregnancy were determined. Prevalence of herbal medicine use in pregnancy was 69.8 %( 363/520). Use of herbal medicine in past pregnancy (PR=3.23, 95% CI=2.23-4.67), believing that herbal medicine is safe (PR=1.1 95% CI=1.01-1.21), and advise by family members to use herbal medicine (PR=1.64, 95% CI=1.04-2.59) were determinants of use herbal medicine during pregnancy. Majority of pregnant women in urban Mulago hospital use herbal medicine to treat common complaints. Further research is needed to document the herbs, their efficacy, and possible effects on birth outcomes.